Manajemen Pengembangan Sumber Daya Manusia Pendidik dan Tenaga Kependidikan dalam Meningkatkan Kualitas di Sekolah - Zainuddin, Zainuddin; Munif, Muhammad (AFKARINA: Jurnal Pendidikan Agama Islam, 2022)
This study aims to obtain an overview of management Human Resource Development at Madrasah Aliyah Negeri (MAN) I Probolinggo which includes: Planning, Organizing, Implementing and Monitoring Programs Human Resource Development. This research uses a case study method with a qualitative approach. The data collected in this study through participatory observation techniques, in-depth interviews, and documentation study. The results showed that: (1) Planning for human resource development programs (teachers) is carried out at the beginning of the new academic year through workshops. The teacher development strategy uses a "make approach", namely education and training. (2) Organizing the HR (Teacher) program is carried out by forming a committee and division of tasks and responsibilities for program implementation. (3) The implementation of the HR (Teacher) development program has been running in accordance with the planning, and (4) Supervision in the implementation of the HR development program (Teacher) is carried out by the principal directly or indirectly through the report of the activity committee.